2019
DOI: 10.18805/ajdfr.dr-1474
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds, Vitamins and Minerals Composition of Freeze-dried Grewia asiatica L. (Phalsa) Pulp and Seed Powder

Abstract: Present study was directed to analyze and compare the bioactive compounds (total phenols, total anthocyanins), vitamins (ascorbic acid, β-carotene, vitamin A), minerals including Ca, Mg, Na, P, K, Fe, Cu, Zn, Co, Mn and heavy metals (Cd, Hg, Pb) of freeze-dried (lyophilized) phalsa pulp and seed powder. In lyophilized pulp powder (LPP) higher amount of total phenols (78.11 mg/100g), total anthocyanin (82.94 mg/100g), ascorbic acid (5.21 mg/100g), β-carotene (0.54 µg/100g), vitamin A (0.89 I.U.) were observed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Arid horticultural crops like Grewia asiatica L. (Phalsa) possess the attributes being sought by the post‐agri‐transformed society of the 21st century. Strong antioxidant, radioprotective, anti‐inflammatory, anti‐cancer, anti‐hyperglycaemic, hepato‐protective, antifungal and antiviral activity and cardioprotective properties of Grewia berries have been recently documented by Bala & Ray (2019) and Mehmood et al . (2020).…”
Section: Introductionmentioning
confidence: 92%
“…Arid horticultural crops like Grewia asiatica L. (Phalsa) possess the attributes being sought by the post‐agri‐transformed society of the 21st century. Strong antioxidant, radioprotective, anti‐inflammatory, anti‐cancer, anti‐hyperglycaemic, hepato‐protective, antifungal and antiviral activity and cardioprotective properties of Grewia berries have been recently documented by Bala & Ray (2019) and Mehmood et al . (2020).…”
Section: Introductionmentioning
confidence: 92%
“…Recent studies have shown that fruits are rich in many bioactive compounds and have high antioxidant capacity and that these chemical components are mostly concentrated in the pulps, peels and seeds of these species (Albuquerque et al, 2016;Vinita and Punia, 2016;Rydlewski et al, 2017;Souza et al, 2018, Stafussa et al, 2018Bala and Barmanray, 2019;Loizzo et al, 2019;Ribeiro et al, 2019;Ousaaid et al, 2020). Several authors have also associated the beneficial effects on human health of regular consumption of fruits, vegetables and grains with the presence of substances as antioxidant potential, such as Potential of the Jerivá Fruit (Syagrus romanzoffiana C.): Physicochemical and Bioactive Characterization phenolic compounds, vitamin C and E and carotenoids (Rababah et al, 2004;Kim et al, 2007;Schreckinger et al, 2010;Donno et al, 2013;Albuquerque et al, 2016;Loizzo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%